Directive speech act in President Joko Widodo's speech related to handling coronavirus (Covid-19) in Indonesia (Pragmatic review) - Desi Novita Sari; Asep Purwo Yudi Utomo (Universitas Negeri Yogyakarta, 2020)
Knowing the type of speech act is very important to understand to see the kind of speech act and its meaning and purpose behind the utterance. The purpose of this study is to describe the types, forms, and meanings or intentions of speech acts in the president's speech related to the handling of the coronavirus, especially with pragmatic studies. The type of research used is qualitative research. This study's data source is the video source contained in the upload of an account on Youtube. The data in this study are all speech acts, which are directive speech acts. The data collection techniques used are recording, observation, observation, and note-taking. The results showed: first, the directive speech acts consist of speech acts by asking, inviting, pleading, ordering, and prohibiting. Second, the speech act is in the form of an oral form, an utterance uttered by the president in his speech regarding the coronavirus's handling, which tends to be qualitative. Third, the purpose of this directive speech act has several meanings, namely to influence, invite, something, tell or explain something, expect attention, forbid, praise, criticize, and as a form of channeling complaints.